Insuficiencia respiratoria grave por gripe h1n1: presentación de un caso fatal - Vázquez, Jorge A.; Borello, Silvina; Saldarini, Fernando; Rodríguez, María Cecilia; Chiacchiara, Daniel N.; Carqueijeda-Román, Gabriel G. (Revista del Hospital Italiano de Buenos Aires, 2011)
.